2018
DOI: 10.1038/s41467-018-03202-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene-by-environment interactions in urban populations modulate risk phenotypes

Abstract: Uncovering the interaction between genomes and the environment is a principal challenge of modern genomics and preventive medicine. While theoretical models are well defined, little is known of the G × E interactions in humans. We used an integrative approach to comprehensively assess the interactions between 1.6 million data points, encompassing a range of environmental exposures, health, and gene expression levels, coupled with whole-genome genetic variation. From ∼1000 individuals of a founder population in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 69 publications
1
80
0
Order By: Relevance
“…While the three island populations differ substantially in terms of genetic composition, we have previously shown that there is a high degree of genetic similarity within islands 13 . Therefore, we may expect that intra-island differences in either DNA methylation or gene expression profiles, if they exist, are likely to reflect local environmental differences 45 . To test this hypothesis, we took advantage of the fact that we collected samples across multiple villages in both Sumba and Mentawai.…”
Section: Resultsmentioning
confidence: 99%
“…While the three island populations differ substantially in terms of genetic composition, we have previously shown that there is a high degree of genetic similarity within islands 13 . Therefore, we may expect that intra-island differences in either DNA methylation or gene expression profiles, if they exist, are likely to reflect local environmental differences 45 . To test this hypothesis, we took advantage of the fact that we collected samples across multiple villages in both Sumba and Mentawai.…”
Section: Resultsmentioning
confidence: 99%
“…The idea that gene-environment interactions (GxE), not the genotype (G) alone, underpin the expression of the phenotype is now well established [1][2][3]. Based on this GxE→P idea, we and others developed a more general concept based on systems biology stating that G is an inheritance system that includes other interacting and heritable components including the epigenome and cytoplasmic components such as mitochondria, Wolbachia, and viruses [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Most human traits are polygenic and their phenotypes are typically influenced by numerous genes and environmental factors, and possibly by their interactions, e.g. genotype-environment (G×E) interaction 1-4 . These traits have been termed as “complex traits”, which are distinguished from Mendelian traits that are shaped by a single or few major genes 5 .…”
Section: Introductionmentioning
confidence: 99%